MARK4 (Microtubule Affinity-Regulating Kinase 4)-Dependent Inflammasome Activation Promotes Atherosclerosis—Brief Report. Issue 8 (August 2019) - Clement, Marc; Chen, Xiao; Chenoweth, Hannah L.; Teng, Zhongzhao; Thome, Sarah; Newland, Stephen A.; Harrison, James; Yu, Xian; Finigan, Alison J.; Mallat, Ziad; Li, Xuan
Abstract : Objective: MARK4 (microtubule affinity-regulating kinase 4) regulates NLRP3 (nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain containing 3) inflammasome activation. The aim of the study is to examine the role of MARK4 in hematopoietic cells during atherosclerosis. Methods and Results: We show increased MARK4 expression in human atherosclerotic lesions compared with adjacent areas. MARK4 is coexpressed with NLRP3, and they colocalize in areas enriched in CD68-positive but α-SMA (α-smooth muscle actin)–negative cells. Expression of MARK4 and NLRP3 in the atherosclerotic lesions is associated with the production of active IL (interleukin)-1β and IL-18. To directly assess the role of hematopoietic MARK4 in NLRP3 inflammasome activation and atherosclerotic plaque formation, Ldlr (low-density lipoprotein receptor)-deficient mice were lethally irradiated and reconstituted with either wild-type or Mark4 -deficient bone marrow cells, and were subsequently fed a high-fat diet and cholesterol diet for 9 weeks. Mark4 deficiency in bone marrow cells led to a significant reduction of lesion size, together with decreased circulating levels of IL-18 and IFN-γ (interferon-γ). Furthermore, Mark4 deficiency in primary murine bone marrow–derived macrophages prevented cholesterol crystal–induced NLRP3 inflammasome activation, as revealed by reduced caspase-1 activity together with reduced production of IL-1β and IL-18. Conclusions: MARK4-dependent NLRP3 inflammasome activation in the hematopoietic cells regulates the development of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.